MANAJEMEN SISTEM INFORMASI DALAM KEGIATAN PENERIMAAN SANTRI BARU DI PONDOK PESANTREN PUTERI KHADIJAH PAMEKASAN - Herliana, Ika; Qosim Mubah, Hilmi; Ahmadi, Ahmadi (re-JIEM (Research Journal of Islamic Education Management), 2021)
This study aims to determine the management of information systems, supporting and inhibiting factors in the acceptance of new students at the Puteri Khadijah Islamic Boarding School Pamekasan. This study uses a qualitative approach with a descriptive type of research. Data obtained from observation, interviews, and documentation. The results showed that first, in managing the information system for admitting new students at the Islamic boarding school, they planned by forming a committee, determining the opening and closing dates, the conditions that must be met, providing website-based forms, and file deposits and evaluating each process carried out. This has been done directly or in writing, after the entire program has been carried out with the evaluation, of course, to find out what is still lacking from the performance to the new student admissions committee then corrected in the future. Second, the supporting factors are the guidance from the caregivers, the direction from the coaches, and also the cooperation of the New Santri Admission committee, completeness of facilities, and infrastructure. The inhibiting factor is the lack of communication between fellow New Santri Admission committees